Transculinary practices of transmigrants in Aleksandar Hemon’s "Blind Jozef Pronek and Dead Souls", "Family Dining" and My Parents: An Introduction/This Does Not Belong to You - Bostič, Nina (Acta neophilologica, 2022)
In the present transnational world populated with transmigrants, food and foodways have assumed a new, hybrid role. In the process of transformation of transmigrant cultural identity of which food and foodways are a central element, the production and consumption of food that is often the result of Svetlana Boym’s reflective nostalgia, may act as a bridge between the homeland and the host land as a material means for maintaining ties with the home country. However, while transmigrant food can assume an inclusive function in their exilic lives, it might also deepen migrants’ sense of displacement and trauma and other them further. The article explores how transmigrants in Hemon’s “Blind Jozef Pronek and Dead Souls”, “Family Dining” and My Parents: An Introduction/This Does Not Belong to You experience food and foodways and what role culinary practices assume in the process of constructing their new, fluid and flexible hybrid identities in Homi Bhabha’s liminal Third Space.
Keywords: bosansko-ameriški pisatelji; eksilne identitete; Hemon, Aleksandar; hrana in prehranjevanje; transnacionalna književnost; transnacionalne kulinarične prakse